Dampak Kredit UMKM dan Tingkat Suku Bunga terhadap Pertumbuhan UMKM di Indonesia - Sasmiharti, Juni; Nurhayati, Meti (Jurnal EMT KITA, 2026)
This study aims to examine the impact of MSME Credit and Interest Rates (BI Rate) on MSME Growth in Indonesia. Using panel data from five provinces during the 2019–2023 period, the study applies the Panel Least Squares method with White cross-section robust standard errors to obtain reliable estimates. The findings reveal that MSME Credit has a positive and significant effect on MSME Growth, confirming that access to productive financing plays a crucial role in enhancing the capacity and performance of micro, small, and medium enterprises. The BI Rate also shows a positive and significant effect, although its contribution is smaller compared to MSME Credit. The model explains 74.69% of the variation in MSME Growth, indicating that both variables serve as key determinants of MSME performance in Indonesia. These results imply the importance of expanding access to productive credit and maintaining monetary stability to support sustainable MSME development.